Post Flood Disaster Infrastructure Development Management In Masamba District, North Luwu Regency - Nuraisyah Nuraisyah; Dandan Haryono (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Masamba and Baebunta District which are located in North Luwu Regency are disaster-prone areas and have a high potential for natural disasters. On July 13 2020, there was a flash flood which damaged infrastructure, public facilities and caused casualties. Until now, the government is still continuing to make improvements. The results of the study indicate that the Management of Infrastructure Development in Masamba District, North Luwu Regency is still experiencing problems. This is due to a lack of estimate regional expenditure revenue-APBD funds which has made infrastructure development unfinished because these funds have been used in handling the Covid-19 virus. To find out how the Management Function of Post Flood Disaster Infrastructure Development in Masamba District, North Luwu Regency. Using the theory of George R Terry which consists of four aspects namely planning, organizing, actuating, and supervising. These four aspects will be used in research to analyze more deeply regarding the research to be carried out. As informants consisted of: PUPR Service, BNPB, Head of Maipi Village, Head of Baloli Village, Head of Bone Village, Old Head of Bone and the Community. This study used interview techniques, observation of research locations, and documentation. Using qualitative methods with descriptive research type.